The effect of Age Toward Learning a Second Language - Endah P. Haryono; Rolina E. Manggopa (Journal of English Language Teaching, Literature and Culture, 2024)
Age has long been perceived as a pivotal factor influencing proficiency in acquiring a second or foreign language. The disparity between child and adult second language (L2) learning is widely acknowledged, with children often deemed more adept and rapid learners compared to adults. The prevailing notion suggests that adults cannot attain native-like fluency in a second language, indicating a potential limitation in adult L2 acquisition. Furthermore, there is a notion of a critical period during which language acquisition is most effective and success in second language learning is attainable. Nevertheless, the debate surrounding this topic has persisted among language researchers for numerous years. This article endeavors to delve into this contentious issue, aiming to elucidate whether the success of second language learning is indeed constrained by age. Through a systematic review methodology within a descriptive qualitative framework, this study examines previous research to discern patterns, insights, and contradictions in the literature regarding the impact of age on second language acquisition. By critically evaluating existing findings, this research aims to contribute to a deeper understanding of the complex relationship between age and proficiency in learning a second language